Energy Democracy and the City: Evaluating the Practice and Potential of Municipal Sustainability Planning - Teron, Lemir; Ekoh, Susan S. (Frontiers in Communication, 2018)
While calls for, and work toward, energy democracy have been entrenched in social movements, and the concept has a burgeoning posture in academic discourse, perhaps the most significant implication for its development is the potential for its implementation at the local governance scale. In order for municipal efforts to be wholly democratic, energy policy must be accessible and responsive to the needs of all communities. This necessitates the convergence of an energy democracy paradigm with principles and practices of both energy justice and just sustainabilities that encourage communities and households’ entrée to the energy planning arena, as participants in policy making and with access to renewable innovations. By using a case study as its means of analysis, this paper will evaluate municipal-scale energy programming by considering the prospects of energy democracy on a sub-state scale. In our analysis of Washington, DC’s sustainable energy utility, we highlight challenges that limit the potential for energy democracy in the nation’s capital, along with practices that lead DC toward energy justice and democracy. We conclude by offering indicators for democratized urban energy planning.